Extension of Time Limit under the Carriage of Goods by Sea Act, B.E.๒๕๓๔ (Thai COGSA) - จันทร์ชีวะ, ประมวล; กองแก้ว, เสกน; ศรีรสระ, ธนกฤติ (Huachiew Chalermprakiet Law Journal, 2012)
Abstract Unavailable